2020
DOI: 10.1515/ijamh-2020-0084
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of waterpipe smoking among high school students in Jakarta, Indonesia

Abstract: ObjectivesThe study aimed to examine factors associated with past 30 days waterpipe use among high school students in Jakarta, Indonesia.MethodsWe surveyed a multistage cluster random sample of 1,318 students of grade 10th and 11th from 14 schools in Jakarta. Multiple logistic regressions were employed to examine the association between past 30 days waterpipe use with sociodemographic characteristics, cigarettes smoking status, parental and peer use, availability and affordability.ResultsOf 1,318 participants,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
(57 reference statements)
0
3
0
Order By: Relevance
“…However, the causal relationship between waterpipe smoking and cigarette smoking should be made with caution because of the cross-sectional design of our study. Two other cross-sectional studies also showed that cigarette smoking was a determinant of adolescent waterpipe smoking, with OR of 3.18 (95% CI = 1.89-5.34) (36), and 6.06 (95% CI = 3.12-11.74) (37). However, a systematic review and meta-analysis based on six prospective cohort studies indicated that waterpipe smoking increased the risk of later initiation of cigarette smoking among young adults, although the definitions were not strict (the definition of waterpipe smoking was based on ever used waterpipe in four studies and cigarette use was also defined based on ever used cigarette in three studies) (38).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…However, the causal relationship between waterpipe smoking and cigarette smoking should be made with caution because of the cross-sectional design of our study. Two other cross-sectional studies also showed that cigarette smoking was a determinant of adolescent waterpipe smoking, with OR of 3.18 (95% CI = 1.89-5.34) (36), and 6.06 (95% CI = 3.12-11.74) (37). However, a systematic review and meta-analysis based on six prospective cohort studies indicated that waterpipe smoking increased the risk of later initiation of cigarette smoking among young adults, although the definitions were not strict (the definition of waterpipe smoking was based on ever used waterpipe in four studies and cigarette use was also defined based on ever used cigarette in three studies) (38).…”
Section: Discussionmentioning
confidence: 90%
“…One study found that smoking of mothers or close friends were significantly associated with adolescent waterpipe smoking ( 39 ). Another study found that waterpipe smoking of family members and friends were positively associated with adolescent waterpipe smoking ( 37 ). Evidence from Lebanon suggested that secondhand smoke exposure and parental smoking were positively associated with adolescent waterpipe smoking ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Globally, influential factors for WPS among youth are commonly associated with their smoking of tobacco and the smoking by family members and friends [16][17][18][19][20]54]. In our study, uses of tobacco other than WPS and alcohol consumption were influential factors for WPS, both lifetime and < 30 days (Figures 1 and 2).…”
Section: Influential Factorsmentioning
confidence: 55%